`What should I do as a coach?`: an interview study with Swedish national team coaches about their professional practice and experiences in addressing potential health risks in elite sport - Hamnlund, C.; Kjær, J. B.; Linnér, S.; Melin, A. (Sport in Society: Cultures, Commerce, Media, Politics, 2024)
Through interviews with 12 Swedish national team coaches, this qualitative study explores the ways in which these coaches experience their professional work in relation to topics such as Relative Energy Deficiency in Sport (REDs) and disordered eating behaviours/eating disorders (DE/EDs). Using Andrew Abbott`s concepts of `diagnosis`, `inference`, and `treatment` as the framework for the study, it suggests that coaches believe they have a role and sufficient knowledge to detect signs and symptoms of REDs or DE/EDs in the diagnosis phase. Following the International Olympic Committee`s guidelines, the coaches prefer to delegate the clinical treatment to members of the athlete`s health and performance team. However, they find that the connection between diagnosis (the problem) and treatment (the action) is unclear, resulting in coaches wanting to `infer` support for their athletes. Implications of these findings are discussed within a professionalisation context along with topics such as education, boundary work, and legitimacy.